SARS-CoV-2 surveillance and detection in wild, captive, and domesticated animals in Nebraska: 2021–2023 - Loy, Duan Sriyotee; Birn, Rachael; Poonsuk, Korakrit; Tegomoh, Bryan; Bartling, Amanda; Wiley, Michael R.; Loy, John Dustin (Frontiers in Veterinary Science, 2025)
Widespread surveillance for SARS-CoV-2 was conducted across wildlife, captive animals in zoological collections, and domestic cats in Nebraska from 2021 to 2023. The goal of this effort was to determine the prevalence, phylogenetic and spatial distribution characteristics of circulating SARS-CoV-2 variants using various diagnostic methodologies that can utilize both antemortem and postmortem samples, which may be required for wildlife such as white-tailed deer. Statewide surveillance testing revealed high variation in SARS-CoV-2 prevalence among species, with white-tailed deer identified as the primary reservoir. In 2021, seroprevalence in white-tailed deer was 63.73% (n = 91) and 39.66% (n = 237) in 2022, while virus detection in retropharyngeal lymph nodes (RLN) was 16.35% (n = 483) in 2021 and 3.61% (n = 277) in 2022. Phylogenetic analysis was conducted on 11 positive samples from 2021. This analysis revealed the presence of four lineages of the Delta variant: AY.100, AY.119, AY.3, and AY.46.4. Conversely, other species showed no virus detection, except domestic cats, which had a low seroprevalence of 2.38% (n = 628) in 2022, indicating minimal exposure. The detection of SARS-CoV-2 in white-tailed deer and the identification of multiple Delta lineages underscores the need for ongoing surveillance and the importance of using different diagnostic methodologies. These efforts are critical for understanding virus circulation and evolution in wildlife and domestic animals, informing public health strategies, and mitigating the risks of zoonotic transmission of SARS-CoV-2 and other emerging infectious diseases.